Environmental Education for Prevent Disaster: A Survey of Students Knowledge in Beginning New Normal of COVID-19 - Feryl Ilyasa; Henita Rahmayanti; Muzani Muzani; Ilmi Zajuli Ichsan; Suhono Suhono (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2020)
The purpose of this study was to determine the importance of implementing disaster mitigation education in schools during the new normal era of coronavirus disease 2019 (COVID-19). The method in this research used descriptive research design using a survey study approach. The research instrument used was a knowledge test with the number of questions as many as 15 items. The sample used was senior high school students who were randomly selected. The level of good and lack of knowledge is determined based on the average total score. A good level of knowledge has a condition> 111.76, while a level of knowledge that lacks a condition <111.76. The results of this study are that the majority of respondents have a total score that is less with a mean score of 101.94, while respondents who have a good number of scores have an average score of 127. Overall respondents have an average of 111.76. Then conducted an Independent Sample t-test with the result that there are differences in the number of good disaster mitigation knowledge scores on respondents with the number of disaster mitigation knowledge scores that are less on respondents with a p-value of 0,000 with a degree of freedom is 95%. The implementation of disaster education in the new normal era is important to continue to prevent transmission of COVID-19. The conclusion of this study is the score of students' knowledge about disaster needs to be improved in the new normal era. Keywords: Disaster Mitigation Education, Disaster Mitigation Knowledge, COVID-19